Non-surgical intervention for palliative treatment in Late-presentation Tetralogy of Fallot (TOF): Is there any hope? - Indah Pratiwi Siregar (Majalah Kardiologi Indonesia, 2025)
Background: Late congenital heart disease (CHD) in patients with tetralogy of Fallot (TOF). Due to the variable severity of defects in patients with TOF, late presentation of CHD may only be discovered beyond the neonatal period. Chronic polycythemia from TOF may increase the risk of hemorrhaging during surgery and patients with untreated TOF risk developing CHD-related pulmonary hypertension. Non-surgical transcatheter palliation in patients with TOF may be applied; however, the efficacy and safety of the method remained very scarce. Therefore, we report two cases of late-presenting TOF treated with non-surgical transcatheter palliation due to high perioperative risks for surgical repair of the defects.